Dirty work on the COVID-19 frontlines: Exacerbating the situation of marginalized groups in marginalized professions - Debus, Maike Elisabeth; Dana Unger; Tahira M. Probst (My University, 2021)
Comments on an article by Cort W. Rudolph et al. (see record 2021-50201-001). As a result of the COVID-19 pandemic, Rudolph et al. argue that frontline health care workers are facing very high levels of job stressors and strains, which may develop into detrimental long-term outcomes. In addition, they point to the heavy burden of jobs in “businesses that continue to provide service to the public” (p. X). Although we agree with these points, we believe that the full costs borne by those working on the COVID-19 frontlines have been understated, as well as the reasons why. In this commentary, we argue that the burden from the global pandemic falls heavily on often marginalized groups working in so-called “dirty jobs” who already face serious preexisting health and socioeconomic disparities. The pandemic has merely exacerbated such preexisting workplace inequalities. To protect these vulnerable workers, we pose potential interventions at the national, community, and organizational levels. We conclude our commentary with thoughts on how we can find a silver lining in the COVID-19 pandemic.